DNAH2 facilitates the homologous recombination repair of Fanconi anemia pathway through modulating FANCD2 ubiquitination. Issue 3 (7th July 2021) - Chang, Lixian; Gao, Xingjie; Wang, Yuxia; Huang, Chunmin; Gao, Min; Wang, Xiaomin; Liu, Chao; Wu, Wenqi; An, Wenbin; Wan, Yang; Zhang, Aoli; Zhang, Yingchi; et al.
Abstract : Abstract: Fanconi anemia (FA), an X-linked genetic or autosomal recessive disease, exhibits complicated pathogenesis. Previously, we detected the mutated Dynein Axonemal Heavy Chain 2 ( DNAH2 ) gene in 2 FA cases. Herein, we further investigated the potential association between DNAH2 and the homologous recombination repair pathway of FA. The assays of homologous recombination repair, mitomycin C (MMC) sensitivity, immunofluorescence, and ubiquitination modification were performed in U2OS and DR-U2OS cell lines. In MMC-treated U2OS cells, the downregulation of the DNAH2 gene increased the sensitivity of cells to DNA inter-strand crosslinks. We also observed the reduced enrichment of FANCD2 protein to DNA damage sites. Furthermore, the ubiquitination modification level of FANCD2 was influenced by the deficiency of DNAH2. Thus, our results suggest that DNAH2 may modulate the cell homologous recombination repair partially by increasing the ubiquitination and the enrichment to DNA damage sites of FANCD2. DNAH2 may act as a novel co-pathogenic gene of FA patients.